Detection of immunological markers for Chlamydia trachomatis and Trichomonas vaginalis infection in women with obstetric complications in Najaf, Iraq - Najim A.Abdulkhudher , et.al (Al-Qadisiyah Journal of Pure Science, 2017)
Infection of female genital tract are associated with many obstetric and gynecological problems include abortion ,intrauterine infection , infertility ,preterm labor and postoperative infection ,in Iraq there is a little study concern with role of both Chlamydia trachomatis , Trichomonas vaginalis and relation with interleukin -6 in different obstetric complications. Hundred women enrolled in this study 60 with different obstetric complications include abortion ,preterm labor and intrauterine death and 40(40%) normal full term pregnancy, full history and examination was done and high vaginal swab was taken for detection of T.vaginalis ( by wet mount preparation and antigen detection).blood was aspirated for detection of antichlamydial antibodies (IgG and IgM) and interleukin-6.The results shows that the diagnosis of T. virginals by antigen detection in vaginal swab more reliable( p<0.001) than direct examination by wet preparation(30.0% and 6.7%) respectively. The presence of C. trachomatis IgG and IgM is (33.3% and 38.3% respectively ) more significant ( p<0.001) in women with obstetric complications in study group than control group (7.5 and 0.0% respectively). The highest level of C. trachomatis IgG and IgM was directly correlated with elevated interleukin -6 (58.3%) in women with obstetric complications.Infection with T.vaginalis and C. trachomatis were associated with increase risk of abortion, preterm labor and intrauterine death , so screening for both infection may reduce different obstetric complications.